Effects of Quetiapine on Neural Tube Development in the Early Stage of Chicken Embryos - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2021)
AIM: To investigate the effects of quetiapine exposure on neural tube development in early stage chicken embryos. MATERIAL and METHODS: Eighty-four fertilised specific pathogen-free chicken eggs were divided into four equal groups (groups 1-4). Three experimental groups (groups 2, 3 and 4) and a single control group (group 1) were used. Each egg in group 2 (n=21) was injected with 20 mu L of saline after 30 hours of incubation. Eggs in groups 3 and 4 were injected with 0.02 ml of a solution containing 400 and 800 mu g of quetiapine dose, respectively. Incubation was continued until the end of 72 hours. All embryos were then removed from the eggs and histopathologically examined. RESULTS: Normal development and the closed neural tubes were shown in 18, 16, 13 and 9 embryos in groups 1 2, 3 and 9, respectively, of the 84 embryos incubated. Open neural tubes were found in one, three and five embryos in groups 2, 3 and 5, respectively. Also, developmental anomalies were found in three, four, five and seven embryos in groups 1, 2, 3 and 4, respectively. Moreover, no significant relationship between NTD and quetiapine exposure had been found. CONCLUSION: Quetiapine has no significant effect on the occurrence of neural tube defects in the chicken embryo model.
Keywords: Quetiapine; Second-generation antipsychotics; Neural tube defect; Spina bifida; Chicken embryo; FOLIC-ACID; ANTIPSYCHOTIC USE; BIPOLAR DISORDER; PREGNANCY; DEFECTS; RISK; WOMEN; MEDICATIONS; PREVALENCE